2010
DOI: 10.1111/j.1600-0897.2010.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinuclear Autoantibodies in Women with Recurrent Pregnancy Loss

Abstract: ANA could be of some value in identifying women with RPL with potential, although still not fully defined, immune abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 41 publications
(80 reference statements)
0
53
0
2
Order By: Relevance
“…Also anyone who tests positive for antinuclear antibody, or anti-thyroid peroxidase, or other autoantibodies even without a confirmed autoimmune disease [13,[20][21][22]. Studies have shown increased rates of these antibodies in RPL patients [2,[23][24][25][26].…”
Section: Diagnostic Criteria Of Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Also anyone who tests positive for antinuclear antibody, or anti-thyroid peroxidase, or other autoantibodies even without a confirmed autoimmune disease [13,[20][21][22]. Studies have shown increased rates of these antibodies in RPL patients [2,[23][24][25][26].…”
Section: Diagnostic Criteria Of Recurrent Pregnancy Lossmentioning
confidence: 99%
“…A recent study suggested that the higher chemokine/cytokine activity during pregnancy in SLE patients increases pregnancyrelated complications and disease fl ares, despite a similar pattern of chemokine/cytokine fl uctuations in healthy pregnant women (5). Pregnancy and SLE aff ect the immune system, increasing the risk of pregnancy-related complications such as abortions, stillbirths, prematurity, preeclampsia, and intrauterine growth retardation (6,7). Antinuclear antibodies at low titers are more common in women with recurrent pregnancy loss (50%) than in controls (16%) (6).…”
mentioning
confidence: 99%
“…Pregnancy and SLE aff ect the immune system, increasing the risk of pregnancy-related complications such as abortions, stillbirths, prematurity, preeclampsia, and intrauterine growth retardation (6,7). Antinuclear antibodies at low titers are more common in women with recurrent pregnancy loss (50%) than in controls (16%) (6). In a recent meta-analysis of pregnancy outcomes in patients with SLE and lupus nephritis, the maternal complications were determined as lupus fl are (25.6%), hypertension (16.3%), nephritis (16.1%), preeclampsia (7.6%), and eclampsia (0.8%).…”
mentioning
confidence: 99%
“…Various immunological disorders have been observed in women with URSA, such as antiphospholipid antibody antibodies, antinuclear antibody (ANA), antithyroglobulin antibody and increased natural killer (NK) cell (Ticconi et al, 2010;Motak-Pochrzest et al, 2013;Youan et al, 2015). Animal studies have found evidence of a link between successful pregnancy and the predominant levels of anti-inflammatory cytokines relative to inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%